Using propensity score matching analysis to compare between cardiometabolic risk factors and physical activity type in Korean adults: findings from a nationwide population-based survey - Min-Hyo Kim; Ji-Won Lee; John A. Linton; Yaeji Lee; Youhyun Song (BMC, 2024)
Abstract Purpose We aimed to assess the effects of different exercise modalities on cardiometabolic risk factors within a comprehensive, representative sample of the Korean population. Methods We categorized 13,971 adult participants into aerobic exercise (AE), resistance exercise (RE), combined aerobic and resistance exercise (TE), insufficient exercise, and inactive groups. Multivariable regressions were conducted to compare the incidence of chronic diseases across the groups before and after propensity score matching (PSM). Results The TE and RE groups had significantly lower waist circumference (WC), mean blood pressure (BP), glucose and insulin-related indices, and white blood cell count (WBC) measures, with TE showing the most significant differences. The TE group had significantly lower triglyceride levels and higher high-density lipoprotein-cholesterol levels. Post-PSM, the TE group had the lowest risk for metabolic syndrome, hypertension, and diabetes, closely followed by the RE group when compared with the inactive group. In a subgroup analysis, RE consistently exhibited benefits including lower body mass index, WC, BP, total cholesterol, glucose and insulin-related indices, and WBC count when compared with AE. RE may be associated with reduced incidence of cardiometabolic diseases compared to AE alone. Conclusion TE appears to be associated with significant reduction in cardiometabolic risk in Korean adults. RE possibly provides a more favorable cardiometabolic effect than AE.